1985
DOI: 10.1111/j.1399-3054.1985.tb04265.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and physiological behaviour of Euglena gracillis cells entrapped in a calcium alginate gel

Abstract: The immobilisation of Euglena gracilis Z cells in a calcium alginate matrix maintained respiratory and photosynthetic activities and ultrastructural integrity. Moreover, immobilization did not prevent Euglena cells from greening inside the gel beads. Electron microscopy demonstrated that the immobilized cells were fixed in the same cellular state as they were when the immobilization occurred. This can he explained by simultaneous reaction of both Ca2+ and the alginate with the cells. Some hypotheses about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 14 publications
(4 reference statements)
2
12
0
Order By: Relevance
“…Such interpretation is extended to the Introduction Very little is known about the mechanisms inducing changes in the metabolic behaviour of immobilized cells (Mattiasson et al 1984). The alginate gelification that is commonly used for the immobilization of photosynthetic cells (Schnabl et al 1983;Robinson et al 1985;Tamponnet et al 1985;Papageorgiou et al 1988) requires the presence of divalent cations at a concentration of 1 0 0 m M ; C a 2+ exhibits the best preservation (Kierstan and Bucke 1977). Previous studies (Tamponnet et al 1985) that have demonstrated the arrest and stabilization of the cellular characteristics of Euolena 9racilis Z cells immobilized by Ca 2+ alginate and stored in darkness at 4 ° C have also suggested an optimal role for the external calcium as compared to other divalent cations.…”
Section: Discussionmentioning
confidence: 99%
“…Such interpretation is extended to the Introduction Very little is known about the mechanisms inducing changes in the metabolic behaviour of immobilized cells (Mattiasson et al 1984). The alginate gelification that is commonly used for the immobilization of photosynthetic cells (Schnabl et al 1983;Robinson et al 1985;Tamponnet et al 1985;Papageorgiou et al 1988) requires the presence of divalent cations at a concentration of 1 0 0 m M ; C a 2+ exhibits the best preservation (Kierstan and Bucke 1977). Previous studies (Tamponnet et al 1985) that have demonstrated the arrest and stabilization of the cellular characteristics of Euolena 9racilis Z cells immobilized by Ca 2+ alginate and stored in darkness at 4 ° C have also suggested an optimal role for the external calcium as compared to other divalent cations.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was removed and fresh fixative added to the pellet of cercariae, which were left at 4°C for 1 hr. The suspension was centrifuged as before, the supernatant removed and the cercariae were concentrated into alginate bead matrices using a method adapted from Kierstan & Bucke (1977) and Tamponnet et al (1985). The cercariae were washed twice in 0.1 M cacodylate buffer (5 min each), spun again, the supernatant removed and 0.5 ml of 5% aqueous sodium alginate added.…”
Section: Methodsmentioning
confidence: 99%
“…Physical techniques have been favoured hitherto, such as entrapment in agar (Kayano et al 1981) and in calcium alginate (Musgrave et al 1982(Musgrave et al , 1983Ochiai et al 1983;Robinson et al 1985;Tamponnet et al 1985), and adsorption in porous polyurethane (Gudin and Thomas 1981;Brouers et al 1982;Muallem et al 1983). Although physical immobilization has the advantage of better maintenance of metabolism and may allow cell proliferation, it has a number of disadvantages, such as the biodegradability of biogels, the incompatibility of calcium alginate with phosphate ions, the tendency of the cells to leak out of the matrix and the opaqueness of polyurethane.…”
Section: Introductionmentioning
confidence: 99%